2020
DOI: 10.1002/anie.201914490
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Catalyzed Cross‐Coupling of Functionalized Alkylzinc Reagents with (Hetero)Aryl Halides

Abstract: A combination of 10 % CoCl2 and 20 % 2,2′‐bipyridine ligands enables cross‐coupling of functionalized primary and secondary alkylzinc reagents with various (hetero)aryl halides. Couplings with 1,3‐ and 1,4‐substituted cycloalkylzinc reagents proceeded diastereoselectively leading to functionalized heterocycles with high diastereoselectivities of up to 98:2. Furthermore, alkynyl bromides react with primary and secondary alkylzinc reagents providing the alkylated alkynes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…22 In principle, there is a substantial body of literature describing Co-based cross-coupling catalysis, 23 and Co I / Co III cycles are oen proposed. [24][25][26][27][28] However, rm mechanistic information remains rather limited. Fout and coworkers analyzed a Co-catalyzed aryl halide amination system in 2014 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…22 In principle, there is a substantial body of literature describing Co-based cross-coupling catalysis, 23 and Co I / Co III cycles are oen proposed. [24][25][26][27][28] However, rm mechanistic information remains rather limited. Fout and coworkers analyzed a Co-catalyzed aryl halide amination system in 2014 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…Lutter and Knochel et al 15 reported an efficient and practical cross coupling from various (hetero)aryl halides and functionalized primary as well as secondary alkylzinc reagents in the catalytic system of 10% CoCl 2 and 20% 2,2′-bipyridine ligands (Scheme 11). In this protocol, the coupling with 1,3-and 1,4-substituted cycloalkylzinc reagents proceeded diastereoselectively to offer functionalized heterocycles with high diastereoselectivities of up to 98:2.…”
Section: Scheme 10mentioning
confidence: 99%
“…The high stability and broad function group tolerance of the organozinc coupling partner contribute to its broad utility. 10 The fast transmetalation (TM) of organozincs with palladium means that this transformation can often be carried out using mild reaction conditions on a wide variety of substrates. Despite the widespread usage of the Negishi CCR, we feel that reaction monitoring methods to probe both the exchange and TM events remain largely underdeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…The Negishi cross-coupling reaction (CCR) has become one of the most versatile tools in synthetic organic chemistry for making carbon–carbon bonds. This reaction couples an organozinc nucleophile and a (pseudo)­halide coupling partner with a Pd catalyst. The high stability and broad function group tolerance of the organozinc coupling partner contribute to its broad utility . The fast transmetalation (TM) of organozincs with palladium means that this transformation can often be carried out using mild reaction conditions on a wide variety of substrates.…”
Section: Introductionmentioning
confidence: 99%